Adaptive control of time-delayed bilateral teleoperation systems with uncertain kinematic and dynamics. Issue 1 (1st January 2019) - Javid, Afshin; Nekoui, Mohammad Ali
Abstract: This paper investigates the adaptive control design problem for time-delayed bilateral teleoperation systems with dynamic and kinematic uncertainties. The majority of the previous investigations in the field of teleoperation systems have only considered the dynamic uncertainties of robots. However, this research studies simultaneous adaptation to both dynamic and kinematic uncertainties. In the presented adaptive control structure, the dynamic and kinematic parameters of the robots are estimated through the proposed adaptive laws and the estimated parameters are utilized to apply amodel-based control law to the teleoperation system. The stability analysis of the teleoperation system with time delay and uncertainties in both kinematic and dynamic parameters is studied based on the Input-to-State Stability (ISS) approach. Simulation results are presented to study the performance of the proposed control structure.